Millennium Development Goal One: How has Asia Fared? - Son, Hyun H. (Journal of Reviews on Global Economics, 2013)
As poverty remains rampant, the Millennium Development Goals have been established to address what is one of the most chronic challenges to growth and development. With numerous governments and international organizations adopting these eight international goals focused on combating both the income and non-income dimensions of poverty, it is imperative to measure the performance toward and success of the MDG initiative. By exploring the interplay among poverty, growth and inequality, this study evaluates the progress of 90 developing countries in attaining the income poverty target contained in the first MDG (MDG1), focusing on developing Asia. To help inform future, results-based development policies, it also examines whether adopting the MDGs has contributed to income poverty reduction by measuring the growth elasticity of poverty, controlling for growth. Through an achievement index developed by Kakwani in 1993, the study estimates that an annual poverty reduction of around 2.77% between 1990 and 2015 is needed for countries to attain MDG1. Across developing Asia, half of the 22 countries included in the study will definitely attain the target and 46% are â€œlikelyâ€ to achieve it. Can such gains in poverty reduction be ascribed to the espousal of the MDGs? The study finds that improvements in poverty elasticity are statistically insignificant in the post-MDG period, implying that the acceleration of poverty reduction has been mainly due to economic growth and not the adoption of the MDGs.